Information Media on Internet Providers Based on 2D Animation - Ida Bagus Andre Putra Dewangkara; Putu Satria Udyana Putra (Jurnal Ekspresi : Desain Komunikasi Visual dan Seni, 2023)
This research endeavors to produce a two-dimensional animated video for the Hinet organization that provides company-related information. The information presented in this two-dimensional animation video comprises the company's products, its benefits, and contact information for potential stakeholders. There are multiple phases involved in the creation of this two-dimensional animation video: pre-production, production, and post-production. The objective of producing this two-dimensional animation video at the Hinet company is to pique public interest in joining the organization, in addition to introducing the company to the general public. This two-dimensional animated video's completion will be disseminated across all social media platforms, including Facebook, Instagram, and others. Based on the responses to the community questionnaire, a significant majority of respondents (98%) expressed confidence in the community's ability to embrace the animated video and concurred that the purpose of its release was to introduce the Hinet company and encourage individuals to become members.